Prevalence of atopic disorders in rheumatic diseases - Karatay, Saliha; Yildirim, Kadir; Ugur, Mahir; Senel, Kazim; Erdal, Akin; Durmus, Bekir; Ozgocmen, Salih (Springer, 2013)
The aim of this study was to assess the point prevalences of hay fever, asthma, and atopic dermatitis in OA, RA, and AS, and to compare with healthy controls. A total of 935 patients and healthy controls were included. Demographic and clinical features were recorded, and a questionnaire assessing the existence of atopic disorders like asthma, hay fever, and atopic dermatitis in all groups was applied. Either atopy implied that an individual was either diagnosed with or had symptoms of one or more of these disorders, such as asthma, hay fever, or atopic dermatitis. When compared to the controls, only patients with AS had an increased risk for hay fever (OR 1.52, 95 % CI 1.00-2.41). Patients with RA had increased risks for hay fever, atopic dermatitis, and either atopy compared to the patients with OA (2.14, 95 % CI 1.18-3.89; 1.77, 95 % CI 1.00-3.18; and 3.45, 95 % CI 1.10-10.87, respectively). Steroid use had no effect on the prevalence of atopic disorders in patients with RA. Patients with OA, RA, and AS seem to have similar risks for asthma, atopic dermatitis, and either atopy to healthy controls. However, the prevalence of hay fever may increase in AS. Patients with RA have a higher risk of atopy than patients with OA.
Keywords: Atopy; Osteoarthritis; Rheumatoid arthritis; Ankylosing spondylitis